Peripheral Sensory Nerve Tissue but Not Connective Tissue Is Involved in the Action of Acupuncture - Chang, Suchan; Kwon, O. Sang; Bang, Se Kyun; Kim, Do-Hee; Baek, Min Won; Ryu, Yeonhee; Bae, Jong Han; Fan, Yu; Lee, Soo Min; Kim, Hyung Kyu; Lee, Bong Hyo; Yang, Chae Ha; et al. (Frontiers in Neuroscience, 2019)
Acupuncture has been used to treat a variety of diseases and symptoms for more than 2500 years. While a number of studies have shown that nerves are responsible for initiating the effects of acupuncture, several lines of studies have emphasized the role of connective tissue in the initiation of acupuncture signals. To determine whether nerve or connective tissue mediates the action of acupuncture, we constructed a robotic acupuncture needle twister that mimicked the twisting of the needle by an acupuncturist, and we examined the role of nerve and connective tissues in the generation of acupuncture effects in rat cocaine-induced locomotion, stress-induced hypertension, and mustard oil-induced visceral pain models. Robotic or manual twisting of acupuncture needles effectively suppressed cocaine-induced hyperactivity and elevated systemic blood pressure or mustard oil-induced visceral pain in rats. These acupuncture effects were completely abolished by injecting bupivacaine, a local anesthetic, into acupoints. However, disruption of connective tissue by injecting type I collagenase into acupoints did not affect these acupuncture effects. Our findings suggest that nerve tissue but not connective tissue is responsible for generating the effects of acupuncture.